Normobaric hypoxia exposure during low altitude stay and performance of elite-level race-walkers - Sikri, G.; Srinivasa, A. B. (Journal of Sports Science & Medicine, 2016)
We read with profound interest the article titled `Increased hypoxic dose after training at low altitude with 9h per night at 3000m normobaric hypoxia` by Carr et al. (2015). Authors have concluded that low altitude (1380 m) combined with normobaric hypoxia of 3000 m improves total haemoglobin mass (Hbmass) and is an effective alternate method for training. Like other studies on elite athletes, the authors of present work have brought out that a major limitation was non-availability of a control group consisting of subjects undertaking same supervised training at normoxia. The total number of `possible` subjects for control group which were taken from a previous study (Saunders et al., 2010) was 11 i.e placebo group (n = 6; 3 male and 3 female) and Nocebo group (n = 5; 3 female and 2 male). It seems likely that authors of the present study have chosen only 10 subjects out of those 11. The criteria for exclusion of one subject and selection of 10 out of 11 subjects from the previous study to form the control group of the present study may require further elaboration.